The role of clinic-based breastfeeding peer counseling on breastfeeding rates among low-income patients - Yetunde Awosemusi; Lauren Keenan-Devlin; Noelle Griffin Martinez; Lynn M. Yee; Ann E. B. Borders (BMC, 2024)
Abstract Background Despite the benefits of breastfeeding (BF), rates remain lower than public health targets, particularly among low-income Black populations. Community-based breastfeeding peer counselor (BPC) programs have been shown to increase BF. We sought to examine whether implementation of a BPC program in an obstetric clinical setting serving low-income patients was associated with improved BF initiation and exclusivity. Methods This is a quasi-experimental time series study of pregnant and postpartum patients receiving care before and after implementation of a BPC program in a teaching hospital affiliated prenatal clinic. The role of the BPC staff included BF classes, prenatal counseling and postnatal support, including in-hospital assistance and phone triage after discharge. Records were reviewed at each of 3 time points: immediately before the hire of the BPC staff (2008), 1-year post-implementation (2009), and 5 years post-implementation (2014). The primary outcomes were rates of breastfeeding initiation and exclusivity prior to hospital discharge, secondary outcomes included whether infants received all or mostly breastmilk during inpatient admission and by 6 weeks post-delivery. Bivariable and multivariable analyses were utilized as appropriate. Results Of 302 patients included, 52.3% identified as non-Hispanic Black and 99% had Medicaid-funded prenatal care. While there was no improvement in rates of BF initiation, exclusive BF during the postpartum hospitalization improved during the 3 distinct time points examined, increasing from 13.7% in 2008 to 32% in 2014 (2009 aOR 2.48, 95%CI 1.13-5.43; 2014 aOR 1.82, 95%CI 1.24-2.65). This finding was driven by improved exclusive BF for patients who identified as Black (9.4% in 2008, 22.9% in 2009, and 37.9% in 2014, p = 0.01). Conclusion Inpatient BF exclusivity significantly increased with the tenure of a BPC program in a low-income clinical setting. These findings demonstrate that a BPC program can be a particularly effective method to address BF disparities among low-income Black populations.